Cell Cycle Progression Determines Wing Morph in the Polyphenic Insect Nilaparvata lugens - Lin, Xinda; Gao, Han; Xu, Yili; Zhang, Yuwei; Li, Yan; Lavine, Mark D.; Lavine, Laura Corley (iScience, 2020)
Wing polyphenism is a phenomenon in which one genotype can produce two or more distinct wing phenotypes adapted to the particular environment. What remains unknown is how wing pad development is controlled downstream of endocrine signals such as insulin and JNK pathways. We show that genes important in cellular proliferation, cytokinesis, and cell cycle progression are necessary for growth and development of long wings. Wing pad cellular development of the long-winged morph was characterized by a highly structured epithelial layer with microvilli-like structures. Cells of adult short wing pads are largely in the G2/M phase of the cell cycle, whereas those of long wings are largely in G1. Our study is the first to report the comparative developmental and cellular morphology and structure of the wing morphs and to undertake a comprehensive evaluation of the cell cycle genes necessary for wing development of this unique, adaptive life history strategy. [Display omitted] •Genes important in determining cell numbers are necessary to form long wings•Long-winged development was characterized by microvilli-like structures•Cells of adult short wing pads are largely in the G2/M phase of the cell cycle•Cells of adult long wing pads are largely in the G1 phase of the cell cycle Biological Sciences; Cell Biology; Developmental Biology; Entomology; Evolutionary Biology